Immunity and inflammatory responses in gilthead sea bream (Sparus aurata L.) exposed to sub-lethal mixture of carbamazepine, cadmium chloride and polybrominated diphenyl ether. Issue 111 (April 2021) - Espinosa-Ruiz, Cristóbal; Manuguerra, Simona; Morghese, Maria; García-Beltrán, José María; Esteban, María Ángeles; Giuga, Marta; Messina, Concetta M.; Santulli, Andrea
Abstract: Chemical contaminants such as industrial and urban by-products, pharmaceuticals, drugs metabolites and, plastics, are continuously found in the oceans, affecting its quality and organism's welfare. Although these compounds are found at concentrations ranged ng L −1, there is an increasing concern about the potential adverse effects of the interactions among those substances present, simultaneously, in a mixture. In the present study, specimens of sea bream ( Sparus aurata ) were exposed, by food, to rising concentrations of a mixture of carbamazepine, polybrominated diphenyl ether-47 and cadmium chloride, for 15 days and then, maintained, with the same control diet, without contaminants, for other 15 days. Samples of skin mucus, serum, head-kidney, liver and intestine were sampled at 0, 15 and 30 days. Cellular immune parameters were evaluated on head-kidney, as well as humoral parameters were determined on skin mucus and serum. In addition, the expression of some genes, related to immunity, was analysed on liver and intestine. Both cellular and humoral response were affected at 15 days, showing slightly signs of recovery at 30 days. Besides, the expression of immune-related genes was highly affected, suggesting the development of inflammatory processes, as well as a reduction of immune parameters. Overall, the mixture of compounds severally affected the immune system of sea bream, suggesting a lower degree of recovery. The prolonged exposure to a mixture of these compounds could entail serious change on population immunity and, eventually, promote changes on marine biota. Graphical abstract: Image 1 Highlights: The effects of mixture of contaminants on marine organisms need to be explored. Rising concentrations of BDE-47, carbamazepine and CdCl2 affected sea bream immunity. Exposure to the mixture of compounds may impair the regulation of inflammation factors. The mixture of compounds compromised the fish defence against pathogens.